Rhetoric of populism in 21st century : Comparative study of German political parties - Bieliková, Tatiana; Eberle, Jakub; Weinfurter, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Populism has emerged in the past year as a significant component of contemporary relations, with populist rhetoric continuously gaining popularity among people. This thesis analyzes the populist discourse of two German political parties, Alternative für Deutschland and Die Linke, in the 2017 federal election, which are the representatives of the far right and far left, respectively, and identifies the most prominent populist elements. Moreover, the thesis offers an outlook on how these narratives shaped the German political scene after the election. The analysis was achieved by a comparative study of these two parties and a discourse analysis of their electoral programs. The empirical part confirmed the hypotheses, as there were several populist elements found in their narratives, mainly anti-establishment, anti-pluralism, focus on identity and simplistic language. Alternative für Deutschland centered their discourse on national identity and anti-immigration policies, while Die Linke focused on social inequality. The thesis proved that the narratives had a significant impact on the German political scene, as Alternative für Deutschland’s narratives ensured its success in the election and managed to sway voters to their side from other parties that were more lenient with their proposed immigration policies. Alternative für Deutschland also appealed to the voters’ dissatisfaction with the current system and presented an image of an outsider willing to fight for its nation, despite some of the party’s radical proposed policies.
Vedoucí práce: Jakub Eberle
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses